2019
DOI: 10.5115/acb.19.031
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of saphenous nerve in cadavers: a guide to saphenous block and surgical interventions

Abstract: The knowledge about detailed morphology and relation of saphenous nerve is important to obtain successful saphenous nerve regional blocks to achieve pre- and post-operative anesthesia and analgesia, nerve entrapment treatments and to avoid damage of saphenous nerve during knee and ankle surgeries. The literature describing detailed morphology of saphenous nerve is very limited. We dissected 42 formalin fixed well embalmed cadaveric lower limbs to explore detailed anatomy, relation and mode of termination of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The terminal and the longest sensory branch of the femoral nerve is the saphenous nerve 13 (Fig 3). In the thigh, within the femoral triangle and adductor canal, the SN lay in a deeper plane in comparison to GSV and remained separated from the vein by a considerable amount of fat, fascia, and sartorius muscle 14 . In the thigh, it courses subfascial and follows the superficial femoral artery 13 .…”
Section: Saphenous Nerve (Sn)mentioning
confidence: 99%
See 2 more Smart Citations
“…The terminal and the longest sensory branch of the femoral nerve is the saphenous nerve 13 (Fig 3). In the thigh, within the femoral triangle and adductor canal, the SN lay in a deeper plane in comparison to GSV and remained separated from the vein by a considerable amount of fat, fascia, and sartorius muscle 14 . In the thigh, it courses subfascial and follows the superficial femoral artery 13 .…”
Section: Saphenous Nerve (Sn)mentioning
confidence: 99%
“…In the thigh, it courses subfascial and follows the superficial femoral artery 13 . Beyond the adductor canal, the SN passed between sartorius and gracilis muscles and became subcutaneous 14 . At the medial aspect of the knee and along with the upper third of the leg, SN and GSV remained separated by connective tissue sleeves of varying thickness ranging 0.5-2.5 cm depending on the thickness of the adipose layer.…”
Section: Saphenous Nerve (Sn)mentioning
confidence: 99%
See 1 more Smart Citation
“…The longest branch of the femoral nerve, the saphenous nerve (SN), supplies sensation to the medial aspect of the knee, leg, and foot. It originates from the femoral nerve within the femoral triangle in the thigh and descends the adductor canal, where it emerges as an infrapatellar branch that goes subcutaneously from the medial to the lateral side below the patella [ 3 ]. It is prone to trauma after surgical procedures around the knee, primarily TKR [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the infrapatellar branch of the saphenous nerve by several knee surgeries results in anteroinferior and medial knee pain [1]. Rousseau et al [2] reported that damage to the recurrent peroneal nerve (RPN) due to increasing internal pressure of the lateral compartment resulted in pain or tenderness to the lateral border of the proximal patellar tendon.…”
Section: Introductionmentioning
confidence: 99%